Cointegration of International Stock Market Indices - Chou, Ray (IMF Working Papers; Working Paper ;, 1994)
In this paper, we derive evidence on the integration of international stock markets from the cointegration properties of international stock market prices. Using the multivariate cointegration test of Johansen, we find that the set of six country stock price indices, including that of the United States, Canada, the United Kingdom, France, Germany, and Japan are cointegrated. The results suggest that there are long-run equilibrium relationships among the stock market prices. Subsample and subgroup analyses also indicate that the cointegration relationships have become stronger over time. This is consistent with greater stock market integration amid the increasing liberalization and globalization of capital markets.